O GESTOR ESCOLAR FRENTE AOS DESAFIOS DA ESCOLARIZAÇÃO DOS ALUNOS COM DEFICIÊNCIA VISUAL - Lievore, Patricia Teixeira Moschen (2020)
The study aimed at analyzing the importance of school manager practice on the articulation of public educational policies directed to visually impaired students in the municipality of Colatina-Espirito Santo State from October 2019 through April 2020 when